The crime of graft and its penalty in Jordanian law: Etymological study compared to the Tunisian law - Abuamer, Hala Taleb (Journal of Economic, Administrative and Legal Sciences, 2021)
This study aims to clarify the concept of the crime of graft in Islamic jurisprudence, Jordanian law and Tunisian law. The study followed the descriptive comparative analytical approach. It also deals with the Qur’an verses and hadiths that prohibited illegal earning and the legal texts criminalizing it. This study clarifies the general elements of this crime, including the presumed element, also the material and the moral elements. The study clarifies the penalties for this crime in both Jordanian and Tunisian law. The study was concluded with a conclusion containing a number of results. The most important of which is that Islamic  law preceded the legal systems and international conventions in the prohibition and criminalization of illicit gain, as well as the criminalization of illicit gain and the arrangement of penalties for it in both Jordanian law and Tunisian law, although the Tunisian law related to illicit gain (enrichment) is more comprehensive and detailed than the Jordanian law in question. In the study, it also recommended a number of recommendations, the most important of which is the need to tighten the penalty in Jordanian law on legal persons when those responsible for it or one of them commits the crime of graft, as well as the need to stipulate the penalty for criminal participation in this law.
Keywords: illegal gain; Islamic jurisprudence; punishment; Jordanian law; Tunisian law